PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA AGEN ASURANSI (STUDI PADA PT PANIN DAI-ICHI LIFE – SUKSES AGENCY) - Sitompul, Pretty Naomi; Winata, Clarrissa; Sihite, Lestari; Ariadi, Eric (Jurnal Kewirausahaan Bukit Pengharapan, 2023)
This research is formulated whether or not there was a significant influence among leadership and motivation toward insurance agent performance at Panin Dai-Ichi Life-Sukses Agency. This research is aimed at figuring out the influence among leadership and motivation toward Insurance Agent performance at Panin Dai-Ichi Life-Sukses Agency. This research was such an quantitative descriptive research. The variables of this research were leadership, motivation, and Insurance Agent. The Population and samples of this research were all the Agent of Panin Dai-Ichi Life-Sukses Agency. Primary data was used as souce of data of this research. The researcher used quesionaires technique to collect the data. To analyze the data, the researcher used the quantitative analysis. The analysis technique used in this research is multiple linear regression analysis. Form the test results of the determination coefficient, the results of R square were 0,713 or 71,3%, which means that influence of the leadership and motivation is influenced by insurance agent performance The results showed that the effect of leadership and work motivation on Insurance Agent performance at Panin Dai-Ichi Life - Sukses Agency.